Analysis of The Effect of Servicescape on Retail Customer Satisfaction - Pramana, I Made Gede Andita; Waluyowati, Nur Prima (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The purpose of this research is to determine the effect of Servicescape on customer satisfaction at GrandLucky Superstore Sunset Road Kuta. The type of this research is explanatory research which explains the position of the variables studied and the influence of one variable on another through hypothesis testing. The number of samples in this study was 102 respondents and the sampling technique used was purposive sampling with the characteristics of the selected sample being at least 18 years old and at least having made purchases more than twice. The test tools used to test research instruments are validity tests, reliability tests and classical assumption tests. The data analysis technique uses multiple linear regression analysis, model accuracy testing uses the f test, and hypothesis testing uses the t test which is calculated using the SPSS program. The research results show that the Servicescape variables consisting of Physical Dimension, Social Dimension, Socially Symbolic Dimension, and Natural Dimension simultaneously have a positive and significant effect on customer satisfaction. However, there is one Servicescape variable, namely the Socially Symbolic Dimension, which does not have a significant effect on GrandLucky Superstore customer satisfaction.